Secular Trend in the Incidence of Japanese Employees with Thyroid Cancer Undergoing Thyroidectomy from 2005 to 2014: a Retrospective Descriptive Study Using an Employment-Based Insurance Claims Database - Yasushi Noguchi; Hisashi Urushihara; Yukinori Sakata; Hitomi Nagamune; Kasumi Daidoji; Mika Ishii; Stewart Geary (Journal of Thyroid Cancer, 2019)
This study aimed to investigate the trend of patients with thyroid cancer undergoing thyroidectomy and those undergoing fine needle aspiration (FNA) and its relationship with thyroid cancer, using a large-scale, real-world database established based on the employment-based health insurance claims data in Japan. In this retrospective descriptive study, annual incidence rates of patients with thyroid cancer undergoing thyroidectomy and FNA from 2005 to 2014 were calculated. Among the 3,130,757 enrollees, 926 patients were diagnosed with thyroid cancer and underwent thyroidectomies. The annual incidence of patients with thyroid cancer undergoing thyroidectomy increased from 5.4 (95% confidence interval 95% CI, 3.4–8.5) in 2005 to 11.7 (10.1–13.5) per 100,000 patient-years in 2013, with a gradual increase among patients in their 20s and 30s and with the most notable increase among those in their 40s and 50s. The annual FNA rate also increased during those years, whereas no noticeable change was observed in the thyroid cancer detection rate. The incidence rates of patients with thyroid cancer undergoing thyroidectomy and those undergoing FNA were strongly correlated, with Pearson’s correlation coefficients of 0.935 for men and 0.886 for women. In conclusion, an increasing trend in the incidence of patients with thyroid cancer undergoing thyroidectomy was observed from 2005 to 2013 among a large group of Japanese employees of working age and their dependents. These results provide useful information on the impact of patients with thyroid cancer undergoing thyroidectomy on the working population.
Keywords: thyroid cancer